Modernity, Minority, and the Public Sphere: Jews and Christians in the Middle East - Goldstein-Sabbah, S.R (Leiden Studies in Islam and Society, 2016)
Modernity, Minority, and the Public Sphere: Jews and Christians in the Middle East explores the many facets associated with the questions of modernity and minority in the context religious communities in the Middle East. Focusing on the Jewish and Christian communities of the Middle East and paying special attention to the concept of space and it's influences on inter-communal dialogues and identity construction this volume presents various examples of how religious communities were perceived and how they perceived themselves. Readership: All interested in the history of the modern Middle East, and anyone interested in questions of Minority, Identity, and the public sphere.